„Beweisgrund“ - Robert Theis (Lexicon Philosophicum)
The paper examines Kant's use of the lexeme “argument” or "proving reason ". As is known, this is prominently featured in the title of his 1762 (1763) paper The Only Possible Argument in Support of a Demonstration of the Existence of God, where it has a programmatic significance. In a first step, the source history will explain the localization of the lexeme in the treatises on the doctrine of reason by George Friedrich Meier and Christian August Crusius, who are reference authors for Kant, (I). Starting from this, Kant's explanations of the lexeme are first presented in his lectures on logic (II 1), then its uses in the published writings (II 2) and in the Nachlass (II 3) are identified and analyzed. In spite of some variations, a high consistency of meaning of the lexeme in the sense of ratio probans is shown.